1978
DOI: 10.1111/j.1600-0773.1978.tb02278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Manganese and Ethanol in Rats

Abstract: The effects of manganese and ethanol interaction on some chemical constituents of the liver and serum of rats were investigated in order to assess the influence of these substances in inducing susceptibility to manganese poisoning. Manganese and ethanol alone or in combination were administered to the rats as drinking solutions for a period of 30 days. Both the chemicals had a synergistic effect in altering the activity of SDH and ATPase in the liver of rats. The combined treatment also produced significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…At the same time, the infl uence of alcohol consumption on Mn status has not been subject to suffi cient research. In particular, earlier experimental studies demonstrated a positive infl uence of alcohol consumption on tissue Mn concentrations (Shukla et al, 1978). Conversely, we have detected a signifi cant decrease in the cord blood Mn concentration in newborns maternally exposed to ethanol.…”
Section: Discussionsupporting
confidence: 43%
“…At the same time, the infl uence of alcohol consumption on Mn status has not been subject to suffi cient research. In particular, earlier experimental studies demonstrated a positive infl uence of alcohol consumption on tissue Mn concentrations (Shukla et al, 1978). Conversely, we have detected a signifi cant decrease in the cord blood Mn concentration in newborns maternally exposed to ethanol.…”
Section: Discussionsupporting
confidence: 43%
“…Of note, consumption of contaminated water from domestic wells has also been found to be a source of Mn toxicity 13, 14 . Due to the incomplete development of the blood-brain barrier (BBB), neonates are at a higher risk of Mn toxicity compared with adult rats 1518 .…”
Section: Introductionmentioning
confidence: 99%